Fishermen and Nets at Husavik Harbor] - Streng, Evelyn Fiedler (1975)
Photograph of fishermen and nets in Husavik Harbor. The group stands on a water-covered, wooden dock along the grey water. Small boats are parked along the dock behind the group of people working with orange and green fishing nets. Grassy hills cover the background with several rectangular buildings and a white church with wooden trimmings and a green roof sat at its foot.